PERSONAL SECURITY IN PUBLIC TRANSPORT - Palo, Jozef (Doprava a spoje, 2008)
Fear of being a victim of some criminal attack is one of the most significant factor discouraging people from public transport usage. It represents a problem in many cities and results from various type of crime (such as physical attack, robberies in vehicles and stops, vandalism etc.). Those carriers who are able to cope with personal security issues and provide physical help and information enjoy respect among their users.